The Band Structure of MnF2 - East, James Albert (My University, 1970)
The Augmented Plane Wave method has been used to calculate the one-electron energy band structure of MnF2 . The bands were computed at the r point and along the ^ line for cases representing the "paramagnetic" and anti-ferromagnetic states of MnF2.
Keywords: augmented, plane wave, band structure, MnF2, energy, electron, states